Identidad Corporativa y su relación con la Imagen Institucional de los colaboradores de la empresa Autonor Nor Oriente S.A.C. en la ciudad de Tarapoto en el año 2014 - Gavidia Silva, Alexander (2015)
This research aimed to determine the level of corporate identity in the company employees Autonort Nor Oriente SAC also its relationship to the institutional image of it was established. To do this we proceeded to develop a questionnaire composed of 23 questions for the variable corporate identity and a questionnaire of 30 questions for the institutional image varying based Moriano, JA authors and others quoting Meyer and Allen (2009) for the first and White painted, Teresa Sanchez Herrera, Joaquin (2013) for the second variable, so that after application of the respective surveys could reach the following conclusions: With respect to Corporate Identity Variable is able to determine the level of affection on the part of employees is high, as the company always provides all the facilities and benefits to its employees to perform professionally. Also the vast majority of employees has plans to continue working in the company, since they consider that the company cares about developing their skills and abilities, also they believe they have invested much effort and time to get the company to reach the level he now owns. Regarding the variable corporate image has been identified that functional Autonort company image is well regarded as large percentage of respondents believe that the infrastructure is appropriate institution for offer the service. Finally we can conclude that the corporate identity is directly related to the corporate image of the company Autonort, since thestaff to feel identified and show actual conduct against the public, create a perfect image of the company therefore customers. They motivated and fully trust the organization because it has created a high degree of confidence